SEBARAN KEPITING MANGROVE (CRUSTACEA: DECAPODA) YANG TERDAFTAR DI KOLEKSI RUJUKAN PUSAT PENELITIAN OSEANOGRAFI-LIPI 1960-1970 - Rianta Pratiwi; Rahmat Rahmat (Research Center for Biology-Indonesian Institute of Sciences, 2015)
Brachyura is a group of Crustaceans species often found in mangrove areas. Mangrove crabs in this study were from mangrove areas found in almost all Indonesian waters that were stored in the Reference Collection of Marine Biota Division, Research Center for Oceanography, Indonesian Institute of Sciences (LIPI) from 1960 to 1970. The aim of this study was to assess the presence and distribution of mangrove crabs from the waters of Indonesia as a search and as a reference collection from 1960 to 1970.A total of 359spesimens were observed, consisted of 54 species, 22 genera, and seven families. The data were stored in a database system to perform spatial information analisys.